Managing Jasapindah.id Instagram Account Effectively to Increase Its Brand Awareness - Sylvia Pratiwi Laiman (Institute of Research and Community Outreach - Petra Christian University, 2019)
Jasapindah.id is a relocation service under PT 3 Permata Logistics management. They provide relocation, packing, and warehouse services. However, the main problem that Jasapindah.id faced was the ineffective use of the social media of Instagram. The current Instagram contents were not good because the information needed was not complete, the quality of the picture was low, and the content was not updated regularly. Hence, the solution was managing its Instagram account by giving comprehensive information, improving the quality of the pictures, and making the content schedules. I improved the Instagram contents and pictures based on the theories from Walter and Gioglio (2014) and Simone (2013). After I managed the account, the brand awareness has increased, as proved by the increasing number of followers and accounts who contacted Jasapindah.id through direct messages and comments. Hopefully, the revised Instagram contents can increase the brand awareness of Jasapindah.id and led to better sales. Keyword: brand awareness, social media, Instagram